Effect of Dodecylbenzenesulfonic acid as a Surfactant on the Properties of Polyaniline/Graphene Nanocomposites. (2019) - Adrian, L.C.O.; Mariatti, M.; Lockman, Z.
Abstract: Polyaniline (PANI) is the most studied conducting polymer because of its conductivity, environmental stability and ease of preparation. This paper reports on the fabrication of PANI by using interfacial polymerisation method. Dodecylbenzenesulfonic acid (DBSA) was used as a surfactant in the synthesis of PANI. Addition of DBSA at 0, 2, 6, and 10 wt % in PANI/graphene nanocomposites was investigated. The structural and morphology of the synthesized PANI are characterized by field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), and ultraviolet-visible spectroscopy (UV-VIS). The thermal stability and electrical properties of the PANI composites were characterized using thermogravimetric analysis (TGA) and a precision resistance meter, respectively. The FESEM images reveal that by increasing amount of DBSA in the synthesis process results in increased of PANI attached on the graphene. FTIR and UV-VIS characterisation shows that the conductive PANI/graphene-DBSA is successfully synthesised using interfacial polymerisation method. Increasing amount of DBSA results in better thermal stability of PANI/graphene-DBSA. The PANI/graphene-DBSA nanocomposite at 10 wt % DBSA loading exhibits the highest electrical conductivity value of 7.31x10 -2 S/cm.